Game DesignTechniques for Software Engineering - Rafaela Marques Pinto de Faria (2016)
Software Engineering is a sub-field of engineering which aims to specify, develop and maintain software systems. It has a wide variety of content, so it is necessary to define the scope and different areas where Software Engineering is found. Thus, IEEE compiled a knowledge base in order to systematize the concepts. As these concepts are very different, it is necessary to approach them differently. A popular way of teaching them is by means of serious games. They have the advantage of motivating the player, allowing a more effective learning experience. For objectively and consistently develope such games, it is necessary to identify a number of patterns and design techniques. In this work we intend to look for the best way of teaching Software Engineering through serious games with the support of game design patterns, by articulating a map with the objectives required for an effective learning. The aim of this research is to develop a map within the sub area of Requirements Engineering where the educational objectives are covered, in order to guide the development of the games with less effort and more systematization.